SOCIALIZATION AS A THREAT: INVERSION IN THE MECHANISM OF SOCIAL CHANGE AND DISORGANIZATION - Dmitry A. Lushnikov (Вестник Северо-Кавказского федерального университета)
The process of socialization, traditionally perceived as a mechanism for developing and reproducing of the social order, is viewed as a mechanism for social change and disruption.